The impact of gender quotas - Franceschet, Susan, 1965-; Krook, Mona Lena.; Piscopo, Jennifer M. (New York ; Oxford : Oxford University Press, 2012)
This text is a theory-building and comparative exercise in elaborating concepts commonly used to analyze the broad impacts of gender quotas. Using a conceptual framework based upon descriptive, substantive and symbolic dimensions of representation, the book presents case studies from 12 countries.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Mar. 5, 2012).
Keywords: Women -- Political activity; Women political candidates -- Government policy; Representative government and representation; Women and democracy